Optical character recognition using deep learning for keyword-triggered value extraction in documents - Lie, Valencia (Nanyang Technological University, 2024)
The manual labour hours needed to compare values within documents remain one of the top inefficiencies that Manufacturing companies like SLB face when performing their regular Quality Control Inspection. On top of that, the risks of errors are high due to its manual handling nature.